Sexual Knowledge and Attitude among Girls Who are Getting Married Based on the Information from Yas Pre-marriage Counseling Center - Baghersad, Zahra (Iran J Nurs Midwifery Res, 2017)
BACKGROUND: High prevalence of sexual dysfunction results from inadequate knowledge or inappropriate attitude toward the natural phenomenon of sexual desire. This study aimed to define sexual knowledge and attitude among girls who were getting married and referred to Yas pre-marriage counseling center. MATERIALS AND METHODS: This research was a descriptive analytical study. The information of 165 girls, who were about to get married, were collected through convenient sampling using a researcher-made questionnaire. Data were analyzed using SPSS version 16 software. Inferential statistical method and Pearson correlation were used for data analysis. RESULTS: Results showed that the mean scores of sexual knowledge and attitude among the participants were 57.42 and 69.02, respectively. There was a significant association between the mean scores of sexual knowledge and sexual attitude (P < 0.001, r = 0.63). CONCLUSIONS: Results showed that the participants had relatively appropriate knowledge and attitude toward sexual relationship.